2018
DOI: 10.1016/j.jalgebra.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Geometry of the word problem for 3-manifold groups

Abstract: We provide an algorithm to solve the word problem in all fundamental groups of closed 3-manifolds; in particular, we show that these groups are autostackable. This provides a common framework for a solution to the word problem in any closed 3-manifold group using finite state automata. We also introduce the notion of a group which is autostackable respecting a subgroup, and show that a fundamental group of a graph of groups whose vertex groups are autostackable respecting any edge group is autostackable. A g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…In this section we use Lemma 4.4 to show that a group that is hyperbolic relative to geodesically biautomatic subgroups is coset automatic relative to each peripheral subgroup with maximal crossover. We note that a similar but weaker SSCA result is shown in [8,Theorem 5.4].…”
Section: Crossover Properties For Relatively Hyperbolic Groupssupporting
confidence: 80%
See 3 more Smart Citations
“…In this section we use Lemma 4.4 to show that a group that is hyperbolic relative to geodesically biautomatic subgroups is coset automatic relative to each peripheral subgroup with maximal crossover. We note that a similar but weaker SSCA result is shown in [8,Theorem 5.4].…”
Section: Crossover Properties For Relatively Hyperbolic Groupssupporting
confidence: 80%
“…Now we provide a description of the language for π 1 (G) that we use in our proof of Theorem A. This is a set of words representing normal forms provided by Higgins in [18], but modified to work with right rather than left cosets, and to provide words over generating sets rather than normal forms that are products of elements; see [8,Prop. 3.3] for more details.…”
Section: Background On Graphs Of Groups and Higgins Normal Formsmentioning
confidence: 99%
See 2 more Smart Citations
“…An autostackable structure for a finitely generated group implies a finite presentation, a solution to the word problem, and a recursive algorithm for building van Kampen diagrams [6]. Moreover, in contrast to automatic groups, Brittenham and Hermiller together with Susse have shown that the class of autostackable groups includes all fundamental groups of 3-manifolds [9], with Holt they have shown autostackable examples of solvable groups that are not virtually nilpotent [7], and with Johnson they show that Stallings' non-F P 3 group [8] is autostackable. In analogy with the relationship between automatic and combable groups, removing the formal language theoretic restriction gives the stackable property for finitely generated groups, and stackability implies tame combability [5].…”
Section: Introductionmentioning
confidence: 99%